2019
DOI: 10.1002/asia.201901124
|View full text |Cite
|
Sign up to set email alerts
|

A Water‐Stable Uranyl Organic Framework as a Highly Selective and Sensitive Bifunctional Luminescent Probe for Fe3+ and Tetracycline Hydrochloride

Abstract: A new coordination polymer (H2bpy)0.5⋅[(UO2)1.5(ipa)2(H2O)] (1) (H2ipa=isophthalic acid, bpy=4,4′‐bipyridine) was synthesized by hydrothermal condition. It was characterized by IR spectroscopy, elemental analysis, TG‐DTA analysis, and powder X‐ray diffraction. Analysis of single‐crystal X‐ray diffraction results showed that the title compound exhibited a double chain bridged by the different uranyl ions and ipa2− ligands. Through the hydrogen bond interactions and π⋅⋅⋅π stacking interactions, the double chains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…and Cr 2 O 7 2À ions, and the quenching mechanism may be similar to those previous reports, 35,36 which was further conrmed by UV-vis spectra (Fig. S7 †).…”
Section: àsupporting
confidence: 89%
“…and Cr 2 O 7 2À ions, and the quenching mechanism may be similar to those previous reports, 35,36 which was further conrmed by UV-vis spectra (Fig. S7 †).…”
Section: àsupporting
confidence: 89%
“…The selective detection toward Fe 3+ by metal–organic frameworks was mainly caused by the interaction between Fe 3+ and the active materials, such as cationic exchange or competing photon absorption between the MOF and the adsorbed ions. Previous reports , have indicated that energy transfer may be a major reason for the quenching of metal ions. The UV/vis spectrum of Fe 3+ exhibited a broad adsorption band λ = 240–380 nm, which had a large overlap with the excitation spectrum of the compounds (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…So far, only one uranyl-based LMOF has been synthesized and utilized as a luminescence sensor in antibiotic detection. 107 An anion 2D layer of (H 2 bpy) 0.5 •[(UO 2 ) 1.5 ( 11a and b). The LOD of U-MOF toward THC was as low as 0.82 ppm, according to the detection limit formula.…”
Section: Uranyl-based Lmofsmentioning
confidence: 99%